(untitled) (Economics and region, 2019)
The essence of the “social responsibility” concept is defined. The process of social responsibility introduction into management of the enterprise personnel is investigated. Existing problems are detected during the implementation of this process at the enterprise. It is established that the important moment for a successful enterprise existence is the usage of socially responsible tools in the personnel management system of the organization. In particular, corporate culture, decent pay, staff development programs, internal communications support, flexible working hours, assistance in emergency situations, etc.